A Matter of Equity: Desegregating and Integrating Gifted and Talented Education for Under-Represented Students of Color. (2nd January 2020) - Ford, Donna Y.; Wright, Brian L.; Trotman Scott, Michelle
Abstract : Access to gifted and talented education (referral, identification, and classes) and advanced classes has been challenging for two student groups of color—Black and Hispanic students. More than 10 years of data from the Office for Civil Rights, Civil Rights Data Collection and numerous reports reveal that discrimination is in operation and gravely compromises access for these gifted students of color. In this article, the authors share data on the aforementioned groups' under-representation, along with desegregation and integration barriers. Our recommendations are guided by equity rather than equality. We call for accountability and deliberate efforts to desegregate and integrate gifted and talented education with excellence and equity fundamental for change. We also draw attention to the Culturally-Responsive Equity-Based Bill of Rights for Gifted Students of Color.